The measurement of space and time in evolving sport phenomena - Fonseca, S.; Diniz, A.; Araujo, D. (Complex systems in Sport, 2014)
This chapter provides an introduction to methods for analyzing both space and time in behavioural data. An overview of methods for analyzing time and, in particular, some methodologies in the so-called time and frequency domains are presented to characterize dynamical behaviours across time. Some important functions, such as the autocorrelation function and the spectral density function, are presented and some illustrations are made. We also present and describe methods for extracting, from a system of interacting agents, spatial time-series data capable of describing underlying dynamic system behaviours. Particular attention is given to applications in team sports. Results from recent studies are considered to illustrate the models presented.